A simulation study of wireless power transfer for electric vehicle - M. M.I., Mohd; Mohd Shafie, Bakar; Mohd Shawal, Jadin (Springer Science and Business Media Deutschland GmbH, 2022)
This study proposes a wireless power transfer (WPT) simulation for electric vehicle (EV) charging. Using the latest WPT technology rather than traditional charging, this study analyses the best way for boosting power transfer in internal combustion engine (ICE) vehicles. In a WPT system for EV applications, compensating circuits are critical for increasing WPT capacity and power transfer efficiency. Compensation topologies such as series-series (SS), series–parallel (SP), parallel-series (PS), and parallel-parallel (PP) each have their own set of advantages and limitations. It is found that, due to their load resistance of 1 kΩ, high coupling coefficient of 0.5, and capacity to operate at 86 kHz, the SP topology is more viable to employ as a composition circuit for WPT system in EV charging.